A voice in the night - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery., 2016)
"Two deaths lead Inspector Montalbano into investigations of corruption and power in the twentieth installment of the New York Times bestselling series. Montalbano investigates a robbery at a supermarket, a standard case that takes a spin when manager Guido Borsellino is later found hanging in his office. Was it a suicide? The inspector and the coroner have their doubts, and further investigation leads to the director of a powerful local company. Meanwhile, a girl is found brutally murdered in Giovanni Strangio's apartment--Giovanni has a flawless alibi, and it's no coincidence that Michele Strangio, president of the province, is his father. Weaving together these two crimes, Montalbano realizes that he's in a difficult spot where political power is enmeshed with the mafia underworld."--